Energetics and Performance of Rice-Wheat as Influenced by Tillage Systems and Moisture Regimes in Inceptisols - R.K. Tomar,; D. Singh,; R.N. Garg,; K.S. Gangwar,; V.K. Gupta,; D. Chakraborty,; R.N. Sahoo,; Rajiv Ranjan,; N.V.K. Chakravarty, (Journal of Soil and Water Conservation, 2022)
Experiments were conducted in split-plot design with eight tillage systems (main-plot) (combinations of two tillage treatments in puddle : 4 and 2 passes of puddler and direct seeded rice &following wheat crops - conventional ; 2 harrowing + 2 cultivator, reduced: 1 harrowing + 1 cultivator) and two moisture regimes (sub-plots): well-watered condition i.e., saturation to submergence (5 + 2.5 cm) in rice and followed by recommended five Irrigations at all physiological growth stages and limited water condition: irrigations at initiation of soil cracking in rice and 3 irrigations at CRI, late jointing and milk stages in wheat. Results revealed that all the energy parameters and productivity of rice as well as succeeding wheat and the system were significantly affected by tillage systems and moisture regimes & interactions were significant. In rice-wheat system, significantly higher energy ratio was found under puddled (5.83) compared to direct seeded (5.16) condition. On the other hand, significantly higher energy ratio was recorded under limited water (5.68) compared to well-watered (5.31) condition. In sandy loam soil, the rice-wheat system has performed exceedingly well under puddled and well-watered condition, as it has given higher energy output and net return of energy compared to direct seeded and well-watered condition as well as higher productivity.